Measurement and evaluation in human performance - Morrow, J. R.; Jackson, A. W.; Disch, J. D.; Mood, D. P. (Human Kinetics, 2011)
Measurement and Evaluation in Human Performance, Fourth Edition, paves the way for students and professionals to identify and solve human performance problems in the areas of kinesiology, physical education, health, and fitness. Focusing on the concepts of reliability, objectivity, and validity, the text introduces students to tests and measurements and guides them through statistical decision making and accurate interpretation of data.